2017
DOI: 10.1186/s13002-017-0140-4
|View full text |Cite
|
Sign up to set email alerts
|

An ethnographic study of salt use and humoral concepts in a Latino farm worker community in California’s Central Valley

Abstract: BackgroundThis article reports on the use of domestic or table salt for its perceived health effects and healing properties in a Latino farmworker community. It explores how contemporary salt usage beliefs can be seen to have roots in long-standing humoral theories of medicine and health.MethodsThis qualitative investigation comprised 30 in-depth individual interviews and five focus groups conducted in Spanish with Mexican and Central American immigrants in one small city in California’s Central Valley (N = 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…We also found evidence of humoral belief systems in women’s discussions about hot–cold food classifications (Barker, Guerra, Gonzalez-Vargas, & Hoeft, 2017). Prior ethnographic work among Puerto Ricans in New York City in the 1970s showed that hot–cold categories of food informed mother’s decisions to feed their infants hot tea and mannitol (a sugary substance) to facilitate feeding transitions from hot to cold foods (Harwood, 1971).…”
Section: Discussionmentioning
confidence: 57%
“…We also found evidence of humoral belief systems in women’s discussions about hot–cold food classifications (Barker, Guerra, Gonzalez-Vargas, & Hoeft, 2017). Prior ethnographic work among Puerto Ricans in New York City in the 1970s showed that hot–cold categories of food informed mother’s decisions to feed their infants hot tea and mannitol (a sugary substance) to facilitate feeding transitions from hot to cold foods (Harwood, 1971).…”
Section: Discussionmentioning
confidence: 57%
“…The utilization of herbals in the treatment of various physiological disorders and diseases goes back to several millennia and more than 60% of the world’s population, especially in the rural areas of developing countries, utilized plants, and other natural products for pharmaceutical and medical aims. In addition, about 25% of modern medications are derived from herbal products and nowadays, the use of natural herbal products has shown an increase in both developed and developing countries [26, 27]. For huge numbers of childless people, infertility disease considered a personal social and psychological problem, which equitably distributed between males and females.…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, the intervention will be designed in a way that allows it to be delivered as part of the yearly FWFHP and can be shared with the Georgia Department of Public Health so that the greatest number of farmworkers can be reached throughout the year. These interventions should also be designed with considerations for cultural beliefs, such as the documented impact of the hot–cold dichotomy on Latino farmworkers’ health and well-being (Barker et al, 2017; McCullagh et al, 2015). These results do not only apply to the development of interventions with heat-exposed workers in Georgia but also support the need for developing heat-illness prevention measures with heat-exposed agricultural workers across the country.…”
Section: Discussionmentioning
confidence: 99%